Voltage-gated sodium channels: from roles and mechanisms in the metastatic cell behavior to clinical potential as therapeutic targets - Sanchez-Sandoval, Ana Laura; Hernández-Plata, Everardo; Gomora, Juan Carlos (Frontiers in Pharmacology, 2023)
During the second half of the last century, the prevalent knowledge recognized the voltage-gated sodium channels (VGSCs) as the proteins responsible for the generation and propagation of action potentials in excitable cells. However, over the last twenty-five years, new non-canonical roles of VGSCs in cancer hallmarks have been uncovered. Their dysregulated expression and activity have been associated with aggressive features and cancer progression towards metastatic stages, suggesting the potential use of VGSCs as cancer markers and prognostic factors. Recent work has elicited essential information about the signalling pathways modulated by these channels: coupling membrane activity to transcriptional regulation pathways, intracellular and extracellular pH regulation, invadopodia maturation, and proteolytic activity. In a promising scenario, the inhibition of VGSCs with FDA-approved drugs as well as with new synthetic compounds, reduces cancer cell invasion in vitro and cancer progression in vivo. The purpose of this review is to present an update regarding recent advances and ongoing efforts to have a better understanding of molecular and cellular mechanisms on the involvement of both poreforming α and auxiliary β subunits of VGSCs in the metastatic processes, with the aim at proposing VGSCs as new oncological markers and targets for anticancer treatments.